Unfolding the Proactive Process for Creativity - Gong, Yaping; Cheung, Siu-Yin; Wang, Mo; Huang, Jia-Chi (Journal of Management, 2012)
The authors integrate the employee proactivity, information exchange, and psychological safety perspectives to develop a model of individual creativity. Proactive employees prepare themselves with resources in anticipation of effecting changes. The authors propose that proactive employees seek informational resources through exchanging with others in the workplace. Information exchange, in turn, fosters the development of trust relationships that provide psychological safety for creative endeavors. The authors collected time-lagged data from a sample of 190 matched employee–manager pairs in a specialty retail chain. The results showed that proactive employees engaged in more information exchange and, by so doing, built stronger trust relationships with supervisors and colleagues. These trust relationships, in turn, increased employee creativity. The relationship between information exchange and employee creativity was fully mediated by trust. The authors discuss the implications of the findings for creativity theory and research.